Sources Of Family Food In Ngurbloat Beach Tourism Area (Case Study Of Ngilngof Village, Manyeuw Sub-District, Southeast Maluku District) - Sesilia Fofid; August Pattiselanno; Maissie Tuhumury (International Journal of Economics, Business and Innovation Research, 2023)
Ngurbloat Beach is one of the famous tourist attractions in Southeast Maluku Regency, this tourist spot is open every day but it is crowded with visitors only on holidays or major holidays so this study aims to determine the source of income for families who are on the tourist area of ​​Ngurbloat beach, Ngilngof Village, Manyeuw District, Southeast Maluku Regency on a day without visitors. The research method used in this study is descriptive qualitative with the analysis used is an interactive model from Miles and Huberman in Sugiyono (2011). Respondents totaling 80 people were determined based on the opinion of Suharsimi Arikunto who stated that, if there are less than 100 research subjects, it is better to take all of them.